Preservice Teachers’ Perspectives on the implementation of Inclusive Education - Bunbun, David Uwumborlame; Owusu, Teddy Afriyie (Universitas Majalengka, 2024)
The study sought to explore preservice teachers’ perspective on the implementation of inclusive education in the university of Education, Winneba, specifically, the department of Special Education. The study employed a phenomenological design. Semi-structured interviews were used to gather data for the study. The population of the study comprised preservice teachers in their final year. The purposive sampling technique was used to select the participants. The sample size of the study was 21 preservice teachers within the department of Special Education. Majority of the respondents perceived that, the implementation of inclusive education is a movement away from segregation, it is a tool for effective inclusive teaching. The study recommends that, Policy makers such as the Ministry of Education should make available copies of the inclusive education Policy book to preservice teachers. This would enable preservice teachers to have indebt knowledge on the policy and as well as its practice. It is also recommended that, the University of Education, Winneba should organize and schedule frequent workshop trainings on inclusive education professional development for preservice teachers.